Can people apply 'FAST' when it really matters? A qualitative study guided by the common sense self-regulation model - Alison Morrow; Christopher B. Miller; Stephan U. Dombrowski (BMC, 2019)
Abstract Background Early identification of stroke symptoms and rapid access to the emergency services increases an individual's chance of receiving thrombolytic therapy and reduces the likelihood of infirmity. The UK's national stroke campaign 'Act FAST' was developed to increase public awareness of stroke symptoms and highlighted the importance of rapid response by contacting emergency services. No study to date has assessed if and how people who experienced or witnessed stroke in line with the campaigns' symptoms of the FAST acronym (i.e., facial weakness, arm weakness, slurred speech, and time) may use this FAST in their response. Methods Semi-structured interviews with 13 stroke patients and witnesses were conducted. Interviews were theory-guided based on the Common Sense Self-Regulation Model, to understand the appraisal process of the onset of stroke symptoms and how this impacted on participants' ability to apply their knowledge of the FAST campaign. Results The majority of patients (n = 8/13) failed to correctly identify stroke and reported no impact of the campaign on their stroke recognition and response. Inability to identify stroke, perceiving symptoms to lack severity and lack of control contributed to a delay in seeking medical attention. Conclusion Stroke witnesses and patients predominantly fail to identify stroke which suggest a lack of FAST application when it matters. Inaccurate risk perceptions and lack of physical control both play central roles in influencing the formation of illness representation not associated with an appropriate emergency response.